MAP/G/1 queue under workload control and postprocessing - Lee, Ho Woo (2013)
This article studies the performance of the MAP/G/1 queue under workload control and post processing. We first obtain the probability generating function of the queue length distribution. Then we derive the mean queue length. We present computational experiences and compare the MAP queue with the Poisson queue.